1999
DOI: 10.1016/s0002-9440(10)65533-2
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Axonopathy in the Brain and Spinal Cord of Transgenic Mice Overexpressing Four-Repeat Human tau Protein

Abstract: Mutations in the human tau gene cause frontotemporal dementia and parkinsonism linked to chromosome 17. Some mutations, including mutations in intron 10, induce increased levels of the functionally normal four-repeat tau protein isoform, leading to neurodegeneration. We generated transgenic mice that overexpress the four-repeat human tau protein isoform specifically in neurons. The transgenic mice developed axonal degeneration in brain and spinal cord. In the model, axonal dilations with accumulation of neurof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
304
2
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 361 publications
(328 citation statements)
references
References 69 publications
20
304
2
2
Order By: Relevance
“…46 Overexpression of protein Tau inhibits kinesindependent trafficking of vesicles, mitochondria, and endoplasmic reticulum in neuro-2a cells, 47 and causes prominent axonopathy in htau-40 transgenic mice. 48 These data strengthen the importance of proper control by posttranslational modification of the microtule-associated protein Tau, its localization, and intracellular concentration, in vivo. We have shown that expression of ApoE4 in neurons results in hyperphosphorylation of protein Tau in brain 37 and in spinal cord (this study).…”
Section: Discussionmentioning
confidence: 56%
“…46 Overexpression of protein Tau inhibits kinesindependent trafficking of vesicles, mitochondria, and endoplasmic reticulum in neuro-2a cells, 47 and causes prominent axonopathy in htau-40 transgenic mice. 48 These data strengthen the importance of proper control by posttranslational modification of the microtule-associated protein Tau, its localization, and intracellular concentration, in vivo. We have shown that expression of ApoE4 in neurons results in hyperphosphorylation of protein Tau in brain 37 and in spinal cord (this study).…”
Section: Discussionmentioning
confidence: 56%
“…2B). The more harmful were tau-(1-44), tau- (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), and tau-(26-230), which reached their maximal neurotoxic effect at an MOI of 50 with only Ϸ20% of cells viable 48 h after infection. By contrast, for tau-(1-156) and tau-(45-230) the survival was 52 Ϯ 2.3% and 72 Ϯ 1.8% (n ϭ 4), respectively, at an MOI of 120.…”
Section: Resultsmentioning
confidence: 99%
“…40 -45 They have tau immunoreactivity in neurons and their processes, but only one study has demonstrated immunolabeling of astrocyte-like cells at the light microscopic level. 42 Another study 43 showed aggregates of 10-to 20-nm straight filaments in myelinated spinal cord axons. The filaments were immunolabeled by antibodies to tau, tubulin, and neurofilaments.…”
Section: Discussionmentioning
confidence: 99%